Unmarried mothers - comparative study - Kirke, Deirdre (Economic & Social Studies, 1979)
This study was designed to identify factors which might be associated with unmarried motherhood in Ireland. One hundred unmarried mothers and a control group of the same number of married mothers were interviewed by the author in the National Maternity Hospital, Dublin in 1973. The results of the study showed that there was no difference between the two groups in their family background or lifestyle but significant differences emerged in three areas (i.e., parental control of dating, attitudes towards premarital sexual intercourse and religious practice).
Keywords: Single parents - Ireland; Mothers - Sociology